2020
DOI: 10.2460/ajvr.81.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical administration of 0.1% diclofenac sodium ophthalmic solution at four frequencies on intraocular pressure in healthy Beagles

Abstract: OBJECTIVE To evaluate effects of topical ophthalmic administration of diclofenac on intraocular pressure (IOP) when applied at 4 frequencies to eyes of Beagles. ANIMALS 8 ophthalmologically normal Beagles. PROCEDURES The study involved four 5-day experimental periods each separated by a 16-day washout period. During each period, 1 drop of 0.1% diclofenac sodium ophthalmic solution was administered to the right eye at 4 treatment frequencies (1, 2, 3, or 4 times/d); 1 drop of eyewash was administered to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It was previously demonstrated that topical flurbiprofen administration induced a small but statistically significant IOP elevation in normal canine eyes compared with the control eye 18 . A recent study with conflicting results regarding the effect of topically applied NSAIDs on IOPs reported no significant effect of topical administration of diclofenac on IOP in normal canine eyes; nevertheless, the same study suggested the topical administration of NSAIDs in eyes with anterior uveitis and a predisposition to high IOP should be carefully considered 14 . In a human study, preoperative administration of diclofenac did not elevate IOP during the early postoperative period following cataract extraction, but the mean IOP increase was higher in the diclofenac group (11.3 and 9.6 mmHg from the baseline in the diclofenac and placebo group, respectively, at 24 h postoperatively) 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously demonstrated that topical flurbiprofen administration induced a small but statistically significant IOP elevation in normal canine eyes compared with the control eye 18 . A recent study with conflicting results regarding the effect of topically applied NSAIDs on IOPs reported no significant effect of topical administration of diclofenac on IOP in normal canine eyes; nevertheless, the same study suggested the topical administration of NSAIDs in eyes with anterior uveitis and a predisposition to high IOP should be carefully considered 14 . In a human study, preoperative administration of diclofenac did not elevate IOP during the early postoperative period following cataract extraction, but the mean IOP increase was higher in the diclofenac group (11.3 and 9.6 mmHg from the baseline in the diclofenac and placebo group, respectively, at 24 h postoperatively) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracameral recombinant tPA is known to be effective in lysing postoperative fibrin, and the use of steroids can suppress postoperative inflammation and prevent fibrin formation 21 . Following phacoemulsification surgery, recurrent inflammation and/or severe fibrin formation is associated with anterior or posterior synechiae, pupillary block, and secondary glaucoma 14 . A recent retrospective study reported that DM was not associated with fibrin formation, but the dog age was associated with fibrin formation 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of topical ophthalmic nonsteroidal anti‐inflammatory drugs (NSAIDs) is essential in preventing and managing uveitis to reduce ocular discomfort in dogs 1,2 . When administered systemically, NSAIDs are an important risk factor for gastrointestinal (GI) bleeding, ulceration, and perforation in dogs 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…Administration of topical ophthalmic nonsteroidal antiinflammatory drugs (NSAIDs) is essential in preventing and managing uveitis to reduce ocular discomfort in dogs. 1,2 When administered systemically, NSAIDs are an important risk factor for gastrointestinal (GI) bleeding, ulceration, and perforation in dogs. [3][4][5] Because the systemic absorption of topical NSAIDs is assumed to be low, these drugs are often given to dogs with other risk factors for GI bleeding, such as concurrent administration of systemic NSAIDs or glucocorticoids, and comorbidities that predispose to GI bleeding and ulceration.…”
Section: Introductionmentioning
confidence: 99%